Land ase analysis for Surabaya metropolitan area urban transportation planning using spatial method - Abidin, Zainal; Prasetijo, Joewono; Mohd Masirin, Mohd Idrus (2024)
The East Java Province, which includes the city of Surbaya, is home to Indonesia's second-largest economic zone. It consists of the cities of Mojokerto and Surabaya as well as the five kabupaten (regencies) of Sidoarjo, Mojokerto, Lamongan, Gresik, Bangkalan, and Kota Mojokerto. There are not less than 9.115.485 peoples in SMA region, so this region categories as Megaurban. SMA is one of the practices of Mega Urban regional development concept. The development concept of SMA then widely to SMS Plus. The teritory of SMA Plus consist of Regency/Menicipality Bojonegoro, Jombang, Pasuruan, dan Tuban. That concept is supported by the acceleration of transportation development such as operational of Suramadu Bridge, Surabaya-Mojokerto Toll Road, and Trans Java Toll Road. The regional and transportation development indeed must be prepared simultaneously, and it must be supported by social, economy and land use data in detailed. The paucity of publicly available data on the geographic land usage by small zone units has made it particularly challenging to obtain this information in Asia and ASEAN countries. Base on the real condition above, the following problem statement are: How the change of land use predicted. How the change of land use will affect to the future transport demand. How the change of land use and transport demand change will affect to the future transport development. this research aims to prepare the effective solution for existing problems of the lack of public geographic land use by small zone units data that will be used for the regional and transportation development planning